2022
DOI: 10.3390/jcm11133752
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Risk of Infection in Patients with Diabetes following Primary Total Knee Arthroplasty: A Global Systematic Review and Meta-Analysis of 120,754 Knees

Abstract: Diabetes mellitus (DM) is a known risk factor for infection following total joint arthroplasty. This study looked at the prevalence and risk of infection in diabetic and non-diabetic patients who had primary total knee arthroplasty (TKA). PubMed, Scopus, Google Scholar, Web of Science, and Science Direct electronic databases were searched for studies published up to 21 April 2022. To compare the risk of infection between diabetic and non-diabetic subjects, a pooled prevalence, and a risk ratio (RR) with 95% co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…Previous studies have demonstrated a strong correlation between diabetes mellitus and infections for PJIs and FRIs [ 12 , 30 ]. Breznicky et al (2020) described a relative risk for PJI between 2.2 and 3.5 depending on the therapy of diabetes [ 27 ], while Ahmand et al (2022) reported in their systematic review a 1.8 times increased risk for patients with diabetes mellitus compared to non-diabetic patients after total knee arthroplasty [ 36 ]. For FRI, as well, an increased risk with a higher rate of diabetes ( p = 0.050) in cases with postoperative infection was detected [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated a strong correlation between diabetes mellitus and infections for PJIs and FRIs [ 12 , 30 ]. Breznicky et al (2020) described a relative risk for PJI between 2.2 and 3.5 depending on the therapy of diabetes [ 27 ], while Ahmand et al (2022) reported in their systematic review a 1.8 times increased risk for patients with diabetes mellitus compared to non-diabetic patients after total knee arthroplasty [ 36 ]. For FRI, as well, an increased risk with a higher rate of diabetes ( p = 0.050) in cases with postoperative infection was detected [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Among these included studies, six reported that diabetes increased the risk ratio of infection, while the other eight showed a null effect of diabetes. Although the authors [ 33 ] demonstrated a significant indication of diabetes as a risk factor, they concluded that the risk is much lower than implied by previously reported data, suggesting that other factors play a larger role in infection in this patient population.…”
Section: Discussionmentioning
confidence: 71%
“…Some of the comorbid conditions previously reported as risk factors for SSI, such as diabetes, metastatic cancer, rheumatoid arthritis, mental disorders, and renal diseases, were not supported in this study, and this result was also reported by several previous investigations [ 5 , 10 , 18 ], particularly in the Chinese population [ 5 , 18 ]. A recent meta-analysis [ 33 ] included 14 studies to calculate the risk of developing an infection in diabetic patients compared to non-diabetic patients following primary TKA. Among these included studies, six reported that diabetes increased the risk ratio of infection, while the other eight showed a null effect of diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…12 Combining surgical interventions with targeted antibiotic therapy tailored to the specific pathogens identified is essential for successful management of PJI. 13 The specter of PJI looms as a formidable burden upon both patients and the healthcare system. Its consequences reverberate through the corridors of medical care, demanding our utmost attention and vigilance.…”
Section: Unveiling the Silent Nemesis: Periprosthetic Joint Infection...mentioning
confidence: 99%